1992
DOI: 10.1017/s0950268800050056
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an agent of the spotted fever group rickettsia from tick eggs in Madrid, Spain

Abstract: Ticks recovered from dogs in rural villages around Madrid (Spain) were processed to isolate rickettsiae. One sample containing mixtures of ticks and four containing eggs, in which rickettsiae had been detected by indirect immunofluorescence with a human serum highly reactive to Rickettsia conorii, were decontaminated, homogenized and inoculated onto Vero cells. Two egg samples yielded a cytopathic agent that reacted positively by immunofluorescence. One sample (14H) was successfully subcultured and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(22). Previous reports of R. rhipicephali in Europe and Africa were based on PCR-restriction fragment length polymorphism profiles compatible with R. rhipicephali after digestion of ompA PCR products obtained from ticks (2,11,16). Thus, further studies based on isolation in cell culture and/or DNA sequencing of PCR products need to be conducted to confirm the presence of R. rhipicephali outside the New World.…”
Section: Discussionmentioning
confidence: 99%
“…(22). Previous reports of R. rhipicephali in Europe and Africa were based on PCR-restriction fragment length polymorphism profiles compatible with R. rhipicephali after digestion of ompA PCR products obtained from ticks (2,11,16). Thus, further studies based on isolation in cell culture and/or DNA sequencing of PCR products need to be conducted to confirm the presence of R. rhipicephali outside the New World.…”
Section: Discussionmentioning
confidence: 99%
“…Reports dealing with the resurgence of MSF in Spain in the early 1980s (31,33,45) have been behind the origin of several clinical studies of the disease and serosurveys in humans and dogs (16,20,22,25,31,(42)(43)(44)(45)(46). So far, the two strains isolated in Spain have been identified as R. conorii in Catalonia and R. rhipicephali in the region of Madrid (17,23,39). For a better knowledge of the epidemiology of SFG rickettsioses in Spain, more rickettsial isolates are needed in order to identify them and compare them with reference strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, by pulsed field gel electrophoresis (PFGE), one of them, the 16B strain, has been found to be identical to R. conorii (39). The only tick isolate obtained in Spain by Vero cell inoculation with eggs of R. sanguineus from dogs near Madrid has been identified, by PCR-restriction fragment length polymorphism (PCR-RFLP) only, as Rickettsia rhipicephali (23). SFG rickettsiae genotypically different from R. conorii have been detected in or isolated from the hemolymph of ticks belonging to the R. sanguineus complex in other Mediterranean countries (1-3, 7, 14).…”
mentioning
confidence: 99%
“…In Spain, the epidemiology of rickettsiae and rickettsial diseases is still poorly described, although several MSF seroepidemiologic surveys [1][2][3] and clinical studies of this disease 4,5 have been reported. The first tick rickettsial isolate was obtained in Spain by Vero cell inoculation with eggs of Rhipicephalus sanguineus isolated from dogs near Madrid and identified by polymerase chain reaction (PCR)-restriction fragment length polymorphism as R. rhipicephali, 6 an SFG rickettsia that seems to be nonpathogenic for humans. In Catalonia, Spain, the first 2 SFG rickettsial strains isolated from humans differed in cytopathogenicity from the reference R. conorii Moroccan strain, 7 although 1 of them, the 16B strain, was identical to R. conorii by pulsed-field gel electrophoresis.…”
mentioning
confidence: 99%